DESIGN AND IMPLEMENTATION OF OPTICAL COMPONENTS AND 3D STRUCTURE OF THIN FILM THICKNESS MEASUREMENT SYSTEM USING ROTATING ANALYZER ELLIPSOMETRY METHOD - Al-Hawari, Muhammad
Thin film plays an important role in many kind of industries, one of them is the semiconductor industry such as microelectronics, photovoltaics, and optoelectronics. In the process of manufacturing and fabrication of semiconductor ICs, most of the steps uses the litography process. Any drop in the quality in the litography process will also means drop in the output of the entire IC fabrication as a whole. Litography process coats thin film after thin film above the substrate used, and then expose it to the UV light to get the desired substrate shape. Inside the coating process, thickness of each thin film must be known to a certain degree, sometimes to the scale of nm. This final project developed ellipsometry method for measuring the nm scale thickness of the thin film. Ellipsometry is a non-invasive, non-destructive, and non-contact method for determining characteristics of thin film. In this method, a light ray is directed into the sample, being reflected, and then read by detector while undergoing an optical modification in the process of its propagation. One modification given is by changing the state of polarization continously, or known as Rotating Analyzer Ellipsometry (RAE). In implementing RAE, one crucial part is the determination of the optical components and the instrument’s structural design, especially on the analyzer rotator part. In this paper, optical components and structural design of rotational component inside RAE.